Expanded graphite – Paraffin composite phase change materials: Effect of particle size on the composite structure and properties. (5th May 2020) - Zhao, Yanqi; Jin, Lu; Zou, Boyang; Qiao, Geng; Zhang, Tongtong; Cong, Lin; Jiang, Feng; Li, Chuan; Huang, Yun; Ding, Yulong
Highlights: Particle size effect of EG on the thermal property of EG/paraffin composite was investigated. Thermal conductivity enhancement of up to 1695% was observed with large particle sizeEG particles. After 50 cycles less than 5 wt% PCM leakage was found with large particle size EG particles. A higher degradation temperature with up to 37 °C increase was observed with small particle size EG particles. Abstract: Expanded graphite (EG) is highly thermally conductive and has a porous structure, making it an ideal candidate for shape stabilisation of phase change materials (PCMs). We investigated the effect of EG size on the structure and properties of EG based paraffin composite PCMs for which no reports have been found in the literature. Large EG particles have a loose vermicular shape with a significant number of pores and voids of irregular shapes and varied sizes, which link together to form a strong networking structure. A higher degradation temperature with up to 31 °C increase was observed for the composite phase change material (CPCM) containing large EG particles, which also showed a significant level of thermal conductivity enhancement of up to 1695% compared with the paraffin. Phase change temperature hysteresis between the melting and solidification was observed on the CPCM made with large EG particles. A higher loading of the EG reduced the temperature hysteresis mainly attributed to a higher heat transfer rate. Fine EG particles are primarily in the form of loose graphite sheets. Such a structure gives a poor thermal cycling stability to composite PCMs containing fine EG particles than that using large EG particles. Composite PCMs made with fine EG particles also has a significantly higher thermal degradation temperature with up to 37 °C increase partially due to interfacial thermal resistance. The fine EG particles give also a good level of thermal conductivity enhancement of up to 340% to the composite PCMs, which is lower than those with large EG particles.